2007
DOI: 10.1073/pnas.0609412103
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of NVP-TAE684, a potent, selective, and efficacious inhibitor of NPM-ALK

Abstract: Constitutive overexpression and activation of NPM-ALK fusion protein [t(2:5)(p23;q35)] is a key oncogenic event that drives the survival and proliferation of anaplastic large-cell lymphomas (ALCLs). We have identified a highly potent and selective small-molecule ALK inhibitor, NVP-TAE684, which blocked the growth of ALCL-derived and ALK-dependent cell lines with IC 50 values between 2 and 10 nM. NVP-TAE684 treatment resulted in a rapid and sustained inhibition of phosphorylation of NPM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
333
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(347 citation statements)
references
References 30 publications
9
333
2
1
Order By: Relevance
“…The exceptional potency of GSK1838705A in ALCL and NSCLC cell lines containing ALK fusion genes and the complete regression of NPM-ALK-dependent tumors in mice with GSK1838705A are encouraging findings for the treatment of cancers driven by oncogenic ALK. These data are consistent with the antiproliferative effects of other ALK kinase inhibitors observed in tumor cell lines harboring ALK fusion genes (18,42,46). In summary, we have shown that GSK1838705A is a potent and selective modulator of IGF-IR activity, with robust antitumor activity in animal xenograft models.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The exceptional potency of GSK1838705A in ALCL and NSCLC cell lines containing ALK fusion genes and the complete regression of NPM-ALK-dependent tumors in mice with GSK1838705A are encouraging findings for the treatment of cancers driven by oncogenic ALK. These data are consistent with the antiproliferative effects of other ALK kinase inhibitors observed in tumor cell lines harboring ALK fusion genes (18,42,46). In summary, we have shown that GSK1838705A is a potent and selective modulator of IGF-IR activity, with robust antitumor activity in animal xenograft models.…”
Section: Discussionsupporting
confidence: 76%
“…Proliferation of ALCL cell lines expressing the nucleophosmin (NPM)-ALK fusion (18,19) was inhibited by GSK1838705A in a concentration-dependent manner (EC 50 s 24-88 nmol/L; Supplementary Fig. S7A; Table 2), whereas FE-PD ALCL cells lacking the fusion (18) were relatively insensitive, with an EC 50 of 4.4 μmol/L (Supplementary Fig.…”
Section: Effect Of Igf-1r/ir Inhibition On Blood Glucose Levelsmentioning
confidence: 99%
“…Crizotinib is a small ALK and c-Met specific inhibitor, which has shown promising results in clinical trials for non-small-cell lung cancer and IMT patients. 26 --32 NVP-TAE684 is a highly specific inhibitor for ALK, 33 and was employed as a complementary inhibitor in these studies. Recently Li et al 34 compared the efficacy of crizotinib with NVP-TAE684 in a NSCLC model and demonstrated that NVP-TAE684 is more potent than crizotinib in inhibiting EML4-ALK oncogenic functions in vitro and in vivo, However, NVP-TAE684 is not currently in clinical trial.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of EML-ALK fusion in NSCLC was confirmed in a number of subsequent studies (14)(15)(16)(17)(18); however, it has not yet been detected in other carcinomas, including breast and colorectal (19,20). A number of EML4-ALK fusion variants have been identified up to date (12,18,(20)(21)(22)(23); all of them involve an almost identical portion of ALK (exons [20][21][22][23][24][25][26][27][28][29] The constitutive kinase activity of ALK is essential for proliferation of ALCL cells and its inactivation represents a feasible therapeutic approach for the treatment of ALCL (24). The intact ALK kinase domain within EML4-ALK possesses marked transforming as well as oncogenic activity in vitro and in vivo, respectively (12,21,25).…”
Section: Introductionmentioning
confidence: 88%